Síntese de precursores de heterociclos e sistemas cíclicos nitrogenados - Silva, Vitor Alcantara Fernandes da (2018)
β-halovinyl ketones are valuable and versatile synthetic intermediates for the synthesis of precious bioactive molecules. Majority of the already described methodologies for the synthesis of these versatile building blocks have focused on transition-metal catalyzed reactions. However, these protocols show some key limitations, as the low stereo- and regiocontrol and the halogen nature (methods only applied to β-clorovinyl ketones). Considering their high synthetic potential, as well as the need of the development of new sustainable methodologies, this work’s main goal was the design and development of a protocol that allows the addition of halogens to ynones for a serene access to β- chlorovinyl ketones. Therefore, it was developed a highly efficient metal-free hydrohalogenation of ynones to obtain β-halo-α,β-insaturated carbonyl systems with high regio- and stereoslectivity and excellent yields.